In search of robust harvest rules for Pacific halibut in the face of uncertain assessments and decadal changes in productivity - Parma, Ana María (2002)
In the conventional ‘assessment-based approach’, catch quotas are calculated as some target harvest rate (not necessarily fixed) applied to a ‘best’ estimate of exploitable biomass produced by the stock assessment. In the alternative ‘management-procedure approach’, quotas are computed from a predetermined feedback control rule, usually a simple algorithm for adjusting catches in response to monitoring indices. Uncertainty and instability of stock assessments complicate the implementation of the conventional approach. For example, estimates of Pacific halibut biomass have changed substantially from year to year, mostly in response to changes in methodology and newly available survey data. Although the changes improved the assessments, the use of an assessment-based approach to set quotas led to unnecessary disruptions in the fishery. Simulations using operating models derived from recent halibut assessments suggest that a management procedure based on a simple delay-difference model could provide stable and adequate yields and perform similarly to two harvesting strategies considered suitable for Pacific halibut (fixed exploitation rate and constant spawning-biomass-per-recruit), implemented assuming no assessment errors. An advantage of such an approach is that once a robust rule is in place, quota setting can be decoupled from assessment, at least until the latter indicates that modifications are needed.